EVALUASI PAPARAN SENYAWA TERFLUORINASI MELALUI PENGGUNAAN KOSMETIK BIBIR WATERPROOF PADA PEREMPUAN USIA SUBUR - Muhammad Nur Alif Johar; Cimi Ilmiawati; Ennesta Asri (SINERGI : Jurnal Riset Ilmiah, 2026)
Waterproof lip cosmetic is a popular innovation due to their long-lasting feature. Research indicates waterproof feature often rely on the addition of fluorinated compounds, substances known as carcinogenic to human and can persist in human. This study aims to evaluate exposure to fluorinated compounds through waterproof lip cosmetics usage among women of childbearing age. Utilizing a quantitative descriptive approach with a cross-sectional design, an online survey was conducted from October to December 2023. The study comprised 334 women of childbearing age, including 101 high school students, 127 university students, and 106 bank employees distributed across West Sumatra, Riau, and West Java using consecutive sampling. Data were gathered through a validated multilevel questionnaire covering demographic profiles, product usage frequency, and specific brands. The research shows that majority of respondents use waterproof lip cosmetics (82.3%), with liquid lipstick as the most prevalent product type (75.8%). Most respondents reported using products 1–5 times per week or more. Product composition analysis indicated that coloring agents were the most frequently components as a potential source of fluorinated compound exposure. Based on the survey and compositional analysis, this study concludes that waterproof lip cosmetics represent a potential source of exposure to fluorinated compounds.